Corneal Cross-Linking with Riboflavin and UV-A in the Mouse Cornea in Vivo: Morphological, Biochemical, and Physiological Analysis - Kling, Sabine (Transl Vis Sci Technol, 2017)
PURPOSE: To morphologically, biochemically, and physiologically characterize corneal cross-linking with riboflavin and UV-A light (CXL) in a newly established in vivo murine model. METHODS: C57BL/6 wild-type mice (N = 67) were treated with various CXL protocols, with modification of the following parameters: total energy (fluence) used, duration of UV-A irradiation, continuous versus pulsed irradiation, and CXL under hypoxic conditions (contact lens). Corneas were evaluated biomicroscopically, histologically, and using optical coherence tomography. Conformational collagen changes were evaluated via changes in the speed of enzymatic digestion. RESULTS: A fluence of 5.4 J/cm(2) induced scar formation, while fluences of < 0.18 J/cm(2) induced neovascularization. Fluences between 1.62 and 2.7 J/cm(2) reduced epithelial thickness, but maintained a transparent cornea after 1 month. Pulsed UV irradiation inhibited neovascularization, but favored scar formation. Changes in the speed of enzymatic digestion suggest that CXL in mice, when compared to humans, requires less UV-A energy than the difference in corneal thickness between the species would suggest. CONCLUSIONS: We demonstrated the in vivo response of very strong and very weak CXL and identified the best suited range of UV fluence in murine corneas. The presented murine CXL model may be helpful in future research addressing cellular and molecular pathways associated to CXL treatment. TRANSLATIONAL RELEVANCE: Adverse tissue reactions following CXL treatment were observed, if the administered UV energy was out of the treatment window—raising concern about novel CXL treatment protocols that have not been previously validated in an experimental setting.